Effect of Theta Burst Stimulation-Patterned rTMS on Motor and Nonmotor Dysfunction of Parkinson's Disease: A Systematic Review and Metaanalysis - Cheng, Bo; Zhu, Tao; Zhao, Wenhao; Sun, Ling; Shen, Yao; Xiao, Wei; Zhang, Shushan (Frontiers in Neurology, 2022)
Background: Theta burst stimulation (TBS), a type of patterned repetitive transcranial magnetic stimulation (rTMS), has several advantages, such as short time of single treatment and low stimulation intensity compared with traditional rTMS. Since the efficacy of TBS on the symptoms of Parkinson's disease (PD) was inconsistent among different studies, we systematically searched these studies and quantitatively analyzed the therapeutic effect of TBS for patients with PD. Methods: We followed the recommended PRISMA guidelines for systematic reviews. Studies from PubMed, EMBASE, CENTRAL, and ClinicalTrials.gov from January 1, 2005 of each database to September 30, 2021 were analyzed. We also manually retrieved studies of reference. Results: Eight eligible studies with 189 participants (received real TBS and/or sham TBS) were included. This metaanalysis found that TBS did not significantly improve Unified Parkinson's Disease Rating Scale part III (UPDRS-III) score in the “on” medicine state (SMD = −0.06; 95% CI, −0.37 to 0.25; p = 0.69; I2 = 0%), while, it brought significant improvement of UPDRS-III scores in the “off” medicine state (SMD = −0.37; 95% CI, −0.65 to −0.09; p < 0.01; I2 = 19%). Subgroup analysis found that merely continuous TBS (cTBS) over the supplementary motor area (SMA) brought significant improvement of UPDRS-III score (SMD = −0.63; 95% CI, −1.02 to −0.25; p < 0.01). TBS had insignificant effectiveness for upper limb movement disorder both in the “on” and “off” medicine status (SMD = −0.07; 95% CI, −0.36 to 0.22; p = 0.64; I2 = 0%; SMD = −0.21; 95% CI, −0.57 to 0.15; p = 0.26; I2 = 0%; respectively). TBS significantly improved slowing of gait in the “off” medicine status (SMD = −0.37; 95% CI, −0.71 to −0.03; p = 0.03; I2 = 0%). Subgroup analysis suggested that only intermittent TBS (iTBS) over the primary motor cortex (M1) + dorsolateral prefrontal cortex (DLPFC) had significant difference (SMD = −0.57; 95% CI, −1.13 to −0.01; p = 0.04). Additionally, iTBS over the M1+ DLPFC had a short-term (within 2 weeks) therapeutic effect on PD depression (MD = −2.93; 95% CI, −5.52 to −0.33; p = 0.03). Conclusion: Our study demonstrated that cTBS over the SMA could significantly improve the UPDRS-III score for PD patients in the “off,” not in the “on,” medicine state. TBS could not bring significant improvement of upper limb movement dysfunction. ITBS over the M1+DLPFC could significantly improve the slowing of gait in the “off” medicine status. Additionally, iTBS over the M1+DLPFC has a short-term (within 2 weeks) therapeutic effect on PD depression. Further RCTs of a large sample, and excellent design are needed to confirm our conclusions.